Rapamycin Protects Skin Fibroblasts From UVA-Induced Photoaging by Inhibition of p53 and Phosphorylated HSP27 - Bai, Gen-Long; Wang, Ping; Huang, Xin; Wang, Zi-Yue; Cao, Di; Liu, Chuan; Liu, Yi-Yi; Li, Ruo-Lin; Chen, Ai-Jun (Frontiers in Cell and Developmental Biology, 2021)
Skin aging caused by UV radiation is called photoaging is characterized by skin roughness and dryness accompanied by a significant reduction of dermal collagen. Rapamycin is a macrolide immunosuppressant which has been shown to exhibit “anti-aging” effects in cells and organisms, however, its roles in the skin photoaging remains unclear. Here, we investigate the role of rapamycin and HSP27, which we have previously identified as an inhibitor of UV-induced apoptosis and senescence in HaCat cells, in a UVA-induced photoaging model of primary human dermal fibroblasts (HDFs). Results from senescence-associated beta-galactosidase (SA-β-gal) staining revealed that rapamycin significantly reduced senescence in UVA-treated HDFs. In addition, treatment with rapamycin significantly increased cell autophagy levels, decreased the expression of p53 and phosphorylated HSP27, and reduced genotoxic and oxidative cellular stress levels in UVA-induced HDFs. Knockdown of HSP27 resulted in a significant increase of MMP-1 and MMP-3 as well as a decrease in type I collagen expression. Rapamycin mitigated these effects by activation of the classical TGF-β/Smad signaling pathway and increasing the transcriptional activity of MAPK/AP-1. Taken together, these results suggest that rapamycin may potentially serve as a preventive and therapeutic agent for UVA-induced photoaging of the skin.